1999
DOI: 10.1007/s002940050465
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a higher-plant chloroplast psbD promoter in a cyanobacterium ( Synechococcus sp. strain PCC7942) reveals a conserved cis-element, designated PGT, that differentially interacts with sequence-specific binding factors during leaf development

Abstract: The chloroplast psbD gene, which encodes the D2 subunit of photosystem II, is regulated by a blue light-responsive promoter (BLRP). We tested the ability of different regions of the barley (Hordeum vulagare) BLRP to drive transcription of the lacZ reporter gene in genomic transformants of Synechococcus sp. strain PCC7942. The barley BLRP was transcribed in Synechococcus from the same initiation sites that are used in plant chloroplasts in vivo. A region of the BLRP, residing between -83 and -112 bp upstream fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…and Nostoc punctiforme ). The distance‐based phylogenetic analysis of complete chloroplastic and bacterial genomes showed that the chloroplast genomes were most closely related to Cyanobacteria (Chu et al , 2004) and chloroplast promoters were shown to initiate gene expression in Cyanobacteria (Dzelzkalns et al , 1984; Christopher et al , 1999). Consequently, homologous recombination could theoretically occur in these strains.…”
Section: Resultsmentioning
confidence: 99%
“…and Nostoc punctiforme ). The distance‐based phylogenetic analysis of complete chloroplastic and bacterial genomes showed that the chloroplast genomes were most closely related to Cyanobacteria (Chu et al , 2004) and chloroplast promoters were shown to initiate gene expression in Cyanobacteria (Dzelzkalns et al , 1984; Christopher et al , 1999). Consequently, homologous recombination could theoretically occur in these strains.…”
Section: Resultsmentioning
confidence: 99%